THRESHOLDS FOR PARTICIPATION IN OPEN ANIMATION PRODUCTION: A CRITICAL EXPLORATION OF SOME ASSUMPTIONS ON PEER-PRODUCTION - Velkova, Julia (AoIR Selected Papers of Internet Research, 2014)
The success of Wikipedia and other large online collaborative projects has led many scholars to speak about the emergence of new forms of production that the Internet has enabled – commons-based peer production, “social production”, crowdsourcing, and produsage which all map a future of an increased user participation in media creation in a landscape of lowered technical and distribution barriers (Benkler, 2006; Castells, 2009; Lessig, 2004; Bruns, 2012). This paper presents a case which challenges the assumption of the easiness to produce media in such alternative ways, and argues for the need to nuance the celebratory discourse adjusting it tighter to the specifics of the different media genres and participatory cultures developed in such an Internet mediated landscape.